2006
DOI: 10.1093/schbul/sbm037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neurocognition and Social Context in Predicting Community Functioning Among Formerly Homeless Seriously Mentally Ill Persons

Abstract: Neurocognition predicts community functioning among homeless persons with severe mental illness, but in a way that varies with the social context in which community functioning occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Four of the included studies (Caplan et al, 2006;Schutt et al, 2007;Seidman et al, 1997;Seidman et al, 2003) were part of the Boston McKinney Project, designed to test the effects of housing on the neuropsychological functioning of severely and persistently mentally ill homeless persons in Boston. In the other studies, unique samples of homeless persons were assessed (Andersen et al, 2014;Bousman et al, 2010;Cotman & Sandman, 1997;Medalia et al, 2003;Pluck, Kwang-Hyuk, David, Spence, & Parks, 2012;Solliday-McRoy et al, 2004;Stergiopoulos, Burra, Rourke, & Hwang, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of the included studies (Caplan et al, 2006;Schutt et al, 2007;Seidman et al, 1997;Seidman et al, 2003) were part of the Boston McKinney Project, designed to test the effects of housing on the neuropsychological functioning of severely and persistently mentally ill homeless persons in Boston. In the other studies, unique samples of homeless persons were assessed (Andersen et al, 2014;Bousman et al, 2010;Cotman & Sandman, 1997;Medalia et al, 2003;Pluck, Kwang-Hyuk, David, Spence, & Parks, 2012;Solliday-McRoy et al, 2004;Stergiopoulos, Burra, Rourke, & Hwang, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Solliday-McRoy et al (2004) considered participants staying in a shelter to be homeless, while others such as Bousman et al (2010) defined homelessness as a dichotomous variable ("ever homeless" and "never homeless") according to set criteria in the Stewart B. McKinney Act of 1987. In half of the studies, the average amount of time that participants had been homeless was not reported (Caplan et al, 2006;Cotman & Sandman, 1997;Medalia et al, 2003;Schutt et al, 2007;Seidman et al, 2003). How the duration of homelessness was reported also varied greatly between studies as can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor outcomes resulting from preventable illnesses, such as viral infection and psychosis (Jones et al, 2015) and geriatric syndromes (Brown, Kiely, Bharel, & Mitchell, 2007) are most appropriate given differential levels of physical and mental health care needs . Relatedly, those with substantial impairments in executive functioning and memory would benefit most from a supportive group home environment as oppose to living alone (Schutt et al, 2007). A practical recommendation moving forward would be to screen for cognitive impairment given the central role of neurocognition in performing complex everyday activities (Gorman et al, 2009;Morgan & Heaton, 2009).…”
Section: Discussionmentioning
confidence: 99%